2019
DOI: 10.1111/micc.12535
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid 4 channels are important regulators of parenchymal arteriole dilation and cognitive function

Abstract: Objective Hypertension‐associated PA dysfunction reduces cerebral perfusion and impairs cognition. This is associated with impaired TRPV4‐mediated PA dilation; therefore, we tested the hypothesis that TRPV4 channels are important regulators of cerebral perfusion, PA structure and dilation, and cognition. Methods Ten‐ to twelve‐month‐old male TRPV4 knockout (WKY‐Trpv4em4Mcwi) and age‐matched control WKY rats were studied. Cerebral perfusion was measured by MRI with arterial spin labeling. PA structure and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The authors then evaluated the role of TRPV4 channels in vessel dysfunction using a TRPV4-knockout rat model [WKY-Trpv4(em4Mcwi)], reporting reduced cerebral perfusion with no changes in parenchymal arteriole structure or myogenic tone. However, these rats did show impaired endothelium-dependent dilation and cognitive function in association with gliosis (Diaz-Otero et al, 2019). It has further been shown that relaxation of VSMCs is diminished in mesenteric arteries of SHR and SHRSP models; this effect was attributed to a decrease in the generation of the endothelium-dependent hyperpolarizing factor, a process that likely depends on TRPV4 and SK channel signaling (Seki et al, 2017).…”
Section: Vascular Risk Factors and The Nvu Hypertensionmentioning
confidence: 91%
“…The authors then evaluated the role of TRPV4 channels in vessel dysfunction using a TRPV4-knockout rat model [WKY-Trpv4(em4Mcwi)], reporting reduced cerebral perfusion with no changes in parenchymal arteriole structure or myogenic tone. However, these rats did show impaired endothelium-dependent dilation and cognitive function in association with gliosis (Diaz-Otero et al, 2019). It has further been shown that relaxation of VSMCs is diminished in mesenteric arteries of SHR and SHRSP models; this effect was attributed to a decrease in the generation of the endothelium-dependent hyperpolarizing factor, a process that likely depends on TRPV4 and SK channel signaling (Seki et al, 2017).…”
Section: Vascular Risk Factors and The Nvu Hypertensionmentioning
confidence: 91%
“…TRPV4 in inflammation and apoptosis. TRPV4 is a non-selective, calcium-permeable cation channel that serves a critical role in cerebral perfusion and inflammation (81). It has been reported that TRPV4 is activated in choroid plexus epithelia and cerebral ischemia by cytokines and inflammatory mediators, such as TNF-α, IL-1β and TGF-β1 (82,83).…”
Section: Role Of Trpv4 In Cerebral Ischemic Injurymentioning
confidence: 99%
“…[59,60] Recently, the relevance of TRPV4 in cerebrovascular function was highlighted when researchers found an impairment in the cognitive function of mice lacking the channel protein. [86,87] Several lines of in vivo evidence indicated that astrocytes can modulate or enhance neuronal oscillations and synchronization, which are both important mechanisms for memory formation, learning, and sensory perception. Activation of astrocytes can also coordinate the activity of neuronal networks and their transition from desynchronized states to synchronized, oscillatory states.…”
Section: Astrocytes and Cognitive Functionsmentioning
confidence: 99%
“…[113] Thus, it would be interesting to explore if P3HT:PCBM blend photostimulation might perturb calcium signaling, cell volume regulation mechanisms as well as actin dynamics in astrocytes. While the nongliotic impact of P3HT:PCBM blend-based retinal implant has been demonstrated in situ, [87] the effect of P3HT:PCBM blend photostimulation in vivo as a gliophotonic interface for cortical astrocytes or for Müller glia in vivo has been completely unexplored.…”
Section: Organic Bioelectronic and Optoelectronic Glial Interfacesmentioning
confidence: 99%